Application Design For New Students Admission In LP3I Surabaya - Setyawan, Mohammad Oby Maulana; Tiowati, Sulis; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
New student admission is important aspect in educational institution that directly connected with registration, entrance test, and admission. New student admission system gives impact for educational institution strategic goals, so that it can produce valid information according to educational institution needs and useful for basis decision making in subsequent development. Current condition in LP3I Surabaya regarding registration, academic test, interest and skill test cannot be held online so every applicants must come right away to do registration and tests.Based on the problem, it can do analyzing and making up application design for new students admission in LP3I Surabaya which is converted to digital and computerized data. To fulfill the need of it, online based system is made for LP3I Surabaya new student admission. This application making started from the beginning communication, planning, modeling, constructing, and operating.After doing trial, new student admission application can handle online registration, academic test and interest skill test online, as to be able to produce accurate data of registration, interest skill test, interview result, test result report, and admission result report. Keywords: application, new student admission, registration.